Synthesis, spectral characterization (FT-IR and NMR) and DFT (Conformational analysis, molecular structure, HOMO-LUMO, UV-vis, NLO) computational studies on 2,2’-((1E,1’E)-phenazine-2,3 dilbis(azanylylidene))bis(methanyly- lidene))diphenol - A, Prabhakaran; E, Dhinesh kumar; D, Rajaraman; M, Arockia doss (International Journal of Advanced Chemistry, 2017)
A new Schiff base was synthesized for the first time by the phenazine-2,3-diamine and 2-hydroxy benzaldedye in ethanol (1:1). The structure of Schiff bases was experimentally characterized by using UV-vis, IR, 1H NMR and 13C NMR spectroscopic methods. Further, the synthesized compound was subjected to DFT for better understanding of the molecular architecture and optoelectronic properties. The optimized geometric parameters supported the available experimental values. The Mulliken and MEP analyses are utilized to identify reactive sites of title molecule. The energetic behaviors of compound 3 in hexane, chloroform, methanol solvents and gas phase were examined using by time-dependent DFT (TD-DFT) method by applying the polarizable continuum model (PCM). The calculated ΔE energies exposed that charge transfer takes place within the molecule. In addition to the polarizability and hyperpolarizability have been calculated which exhibit that compounds possess non-linear optical nature.